Teaching basic life support for medical students: Assessment of learning and knowledge retention - Nara Lúcia de Carvalho Silva; Maria do Carmo Barros de Melo; Priscila Menezes Ferri Liu; João Paulo Ramos Campos; Marina de Abreu Arruda (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Education mediated by simulation is a widely used method for teaching basic life support (BLS). The American Heart Association recommends protocols based on scientific evidence to reduce sequelae and mortality. We aimed to assess learning and retention of knowledge of BLS in students of the first semester of the medical course using teaching methods of dialogic expository class (group 1), expository and demonstrative class (group 2), and the two previous methodologies associated with simulated practice (group 3), and after 3 months, memory retention. MATERIALS AND METHODS: This was an experimental, prospective, randomized study. Participants were assessed in terms of performance in theoretical and simulated practical tests, satisfaction with training (Likert scale), and knowledge retention. RESULTS: The practical test results were analyzed by two experienced observers. Students had 20% progression in knowledge and 80% retention of knowledge after 3 months of exposure comparing the theoretical pre- and posttest. The students in group 3 performed better than the others (P = 0.007) in the posttest. With the simulated practice, the knowledge acquired was maintained after 3 months with a mean performance of 90%, but in the test of the infant age group, there was a loss of learning retention by 10%. There was no difference of the results between the two evaluators (P < 0.001). The training was positively assessed by the participants. CONCLUSION: The use of different methodologies promoted knowledge progression, with emphasis on simulated practice. Learning retention was maintained after 3 months. In order to teach BLS to infants, it may be necessary to improve teaching techniques.